The Influence of Health Coaching Colling on the Intention to use Healthy Latrines Coastal Communities - Ayu Dewi Nastiti; Erik Kusuma; R.A. Helda Puspitasari; Dwining Handayani (Jurnal Keperawatan, 2024)
Intention to use healthy latrines is still found in the community, the low intention of the community to use latrines can trigger or cause open defecation (BAB) habits. The main factor that causes the community's low intention to practice healthy latrines is the lack of knowledge, so that people's awareness of defecating is still poor. Health coaching education is a strategy that can be used as an intervention to encourage and empower people to choose healthier lifestyles by promoting better condition management.  The purpose of this study was to determine the influence of helath coaching colling on intention to use coastal community healthy latrines for pasuruan city. In this study using a pre-experimental research design with a research design One group pre-test-post test design. Where in this study it was carried out in a way before being given treatment/treatment, the variables were observed/measured first (pre-test) after that the treatment/treatment was carried out and after the treatment was carried out measurement/observation. The population in this study were all residents in the Tapaan Sub-District, Pasuruan City, totaling 3,255 samples in this study consisting of 43 people, where the sample was obtained using simple random sampling. The results showed that 43 respondents who originally intended to use the latrine were sufficient, with 26 respondents (60.5%). After being given health coaching colling, almost all of them showed that 39 respondents (96.8%) had good intentions. The results of the Wilcoxon statistical test obtained a value of p = 0.000 ˂ α = 0.05, so H1 was accepted, meaning that there was an influence between "the effect of health coaching colling on the intention to use healthy latrines in Tapaan Village. From the research results is strengthened based on the results statistical analysis indicating the presence the influence of health coaching colling on the intention to use healthy latrines. In the opinion of Oliveira et al., (2017) given health coching colling with an intensive period of time able to increase the intensity in latrine use.